PERBEDAAN STABILITAS DIMENSI ANTARA CETAKAN ALGINAT YANG DIBERI DESINFEKTAN EKSTRAK DAUN ALPUKAT (Persea americana mill) DENGAN NATRIUM HIPOKLORIT - An Nisaa Amelia; Netti Suharti; Eni Rahmi (Faculty of Dentistry Universitas Andalas, 2017)
Background : Alginat is one of the most used impression material in dentistry.. Alginate impression need to be disinfected to prevent cross-infection. One of effective natural material that can be used as disinfectant is avocado leaves. The process of disinfection could interfered the dimensional stability of alginate impression caused of imbibition properties in alginate itself. Purpose : To determine the differences of dimensional stability of alginate impression which disinfected with avocado leave extract 100% compared 0.5% sodium hypochlorite. Method : This research was an experimental laboratory with post -test only control group design. Sample were divided into 3 groups, 1 group were sprayed with aquadest as control group and 2 treatment groups were sprayed with avocado leaves extract 100% and 0.5% sodium hypochlorite and stored for 10 minutes. The impression then casted with gypsum in cylinder mold and diameter of the cast were measured. The One Way ANOVA test were used to determine the dimensional stability of the difference between the groups. Result :The results showed that the alginate impression which disinfected with avocado leaves extract 100% have a significant dimensional change, that is 0.123 ± 0.011 mm compared with 0.5% sodium hypochlorite only 0.034 ± 0.011 mm. Conclution : There are differences in dimensional stability of alginate impression which disinfected with avocado leaf extract 100% and 0.5% sodium hypochlorite. Keywords:Dimensional stability, avocado leaves extract, and sodium hypochlorite